2018
DOI: 10.1016/j.jjcc.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Distal radial arterial hypertrophy after transradial intervention: A serial intravascular ultrasound study

Abstract: Serial IVUS of the distal RA revealed a significant increase in IMV and decreases in LV and VV. Diabetes was the most powerful independent predictor of the percentage change in IMV of the distal RA after TRI. The percentage change in IMV was significantly positively correlated with HbA1c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Post-catheterization stenosis and occlusion of the radial artery are common and related to several factors, including female sex, age, manual compression, and radial artery diameter [50]. Wakeyama et al [51] found radial artery hypertrophy after transradial intervention by IVUS. After 6 months, the intima-media volume in patients who underwent transradial artery intervention was increased significantly, whereas the lumen volume and vessel volume decreased significantly.…”
Section: Raomentioning
confidence: 99%
“…Post-catheterization stenosis and occlusion of the radial artery are common and related to several factors, including female sex, age, manual compression, and radial artery diameter [50]. Wakeyama et al [51] found radial artery hypertrophy after transradial intervention by IVUS. After 6 months, the intima-media volume in patients who underwent transradial artery intervention was increased significantly, whereas the lumen volume and vessel volume decreased significantly.…”
Section: Raomentioning
confidence: 99%
“…The resolutions of Doppler ultrasound in low-and high-frequencies ranging from 8 MHz to 50 MHz can detect the properties of blood flow, which can operate in A-and B-scan modes. Intravascular ultrasound catheters have permitted tomographic visualization to reveal the cross section of arterial vessels, such as coronary artery, with a diameter of <0.9 mm [39]- [41]. However, it is an invasive imaging technology for scanning the intimal layer of vessels.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Progressive luminal narrowing of the radial artery has been reported following transradial procedures. Studies using intravascular ultrasound, optical coherence tomography, or histology have demonstrated alterations of the radial artery such as intimal damage, inflammation, and medial dissection after TRA coronary interventions 25–28. These endothelial changes may trigger a cascade of events promoting thrombus formation acutely as well as intimal hyperplasia with progressive narrowing over time.…”
Section: Discussionmentioning
confidence: 99%